Decentralized Management of Hybrid Energy Systems Considering Uncertainty - Leonard Pin, Lee Shaw; Ahmed Mohamed, Ahmed Haidar; SOPRONI, Vasile-Darie (Editura Universitati din Oradea, 2024)
The main challenge in many countries is how to deal with climate change, particularly reducing CO2 emissions which is the most crucial aspect. Therefore, this paper focuses on adopting renewable energy in a fuel cell microgrid connected with hybrid energy storage systems. A control management approach based on state machines is introduced to regulate the combined renewable generation with hybrid energy storage systems. The operational performance of the microgrid has been evaluated under various conditions, including different weather patterns and the energy needs of local villagers. The key contribution of this work is aimed at addressing the region's unique issues in rural electrification and climate change mitigation. The results of microgrid stability in energy supply, mainly in off-grid scenarios affirm the system's practical viability and reliability.